2021
DOI: 10.3389/fenvs.2021.723166
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Solutions for Urban Climate Change Adaptation and Wellbeing: Evidence and Opportunities From Kiribati, Samoa, and Vanuatu

Abstract: Climate change and urbanisation in combination put great pressure on terrestrial and ocean ecosystems, vital for subsistence and wellbeing in both rural and urban areas of Pacific islands. Adaptation is urgently required. Nature-based solutions (NbS) offer great potential, with the region increasingly implementing NbS and linked approaches like ecosystem-based adaptation in response. This paper utilises three Pacific island nation case-studies, Kiribati, Samoa and Vanuatu, to review current NbS approaches to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This could be done by building on and further connecting ongoing efforts to centralise knowledge regionally. Examples include the Urban Nature Atlas focusing initially on Europe 18 , and extending later to other regions through participatory approaches 58 , or the emerging Kiwa Initiative focusing on NbS in Oceania 59 .…”
Section: Discussionmentioning
confidence: 99%
“…This could be done by building on and further connecting ongoing efforts to centralise knowledge regionally. Examples include the Urban Nature Atlas focusing initially on Europe 18 , and extending later to other regions through participatory approaches 58 , or the emerging Kiwa Initiative focusing on NbS in Oceania 59 .…”
Section: Discussionmentioning
confidence: 99%
“…As the third aspect, supervision emphasizes an ILK-led monitor pattern that enhances the adaptability and resilience of NbS [1,36]. Last, but not least, a general participation of indigenous people and local communities is also considered critical for just NbS, the scope of which covers the aforementioned three aspects, as well as extra possible descriptions, including community co-creation, full participation, and co-production [11,14,15].…”
Section: Ilk-integration Frameworkmentioning
confidence: 99%
“…ILK can be an impactful tool in this aspect. International reports and academic studies have shown that indigenous people provide a source of knowledge for climate adaptation, biodiversity conservation, urban and rural resilience enhancement, and disaster control [3,15]. For instance, the IPCC Sixth Assessment Report stated with high confidence that planning processes that integrated ILK and scientific knowledge could effectively prevent maladaptation and control consequent risks to marginalized and vulnerable groups [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some NbS investment is large scale. The Kiwa Initiative, for example, launched in 2020, is a major 35 million euro multi-donor NbS programme led by the Agence Française de Développement that will fund various NbS projects at different scales across Pacific islands, expecting to include urban areas [69]. NbS initiatives in Oceania have showcased feasible approaches to a number of broad challenges including: climate change mitigation and adaptation; biodiversity conservation; disaster risk reduction; management of coastal areas; water, food and energy security; human physical and psychological health issues, such as air quality, green space management, and public health; poverty reduction; social justice; participatory planning and governance; and sustainable economic and social development in general (ibid).…”
Section: Experience From Oceaniamentioning
confidence: 99%